Keefektifan Cara Pembinaan Kepala Sekolah dan Sikap Profesional Guru SMU - Petrus Engko (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This study expost facto was intended to find effective ways of developing techers’ professionalism. Data were collected from eighty high school teachers in Ambon by using questionnaire, and analyzed by using descriptive statistics and product moment correlation. The result showed that principals’ ways of guiding teachers were sufficiently effective, but they could not be used to predict teachers’ professionalism. Principals were expected to continue creating conducive learning atmosphere for teachers and students.